Benefits of maternal pectin supplementation in gestation diet on vaginal microbiota of sows and intestinal health of newborn piglets - He, Jiaqi; Zheng, Jie; Huang, Yingyan; Li, Shuang; Hua, Lun; Jiang, Xuemei; Che, Lianqiang; Fang, Zhengfeng; Feng, Bin; Lin, Yan; Xu, Shengyu; Li, Jian; et al. (Frontiers in Veterinary Science, 2024)
Pectin is a proven prebiotic and widely used in human health products. This study aims to assess the impact of dietary pectin supplementation during gestation on sow vaginal microbiota and the offspring's intestinal composition. Thirty sows were randomly allocated to two groups and fed a standard diet (CON) or a standard diet supplemented with 3 g/kg pectin (PEC). Blood, feces, and vaginal swab samples from the sows and blood, intestines issue, and colonic content samples from the offspring were collected and analyzed. The results indicate that the relative abundance of vaginal Lactobacillus was notably enhanced in the PEC group and fecal β-glucuronidase (β-G) activity and plasma 17β-estradiol (E2) concentration were also significantly increased in the PEC group. Newborn piglets were found to host different microbial communities as well. At the phylum level, Proteobacteria dominated in the CON group, and Firmicutes was predominant in the PEC group. Newborn piglets in the PEC group had a lower interleukin-6 (IL-6) concentration in their plasma. The expression of intestinal cytokines of offspring was improved as well. Villus height and villus height/crypt depth (V/C) in the PEC group were extremely higher than those in the CON group. In conclusion, dietary pectin supplementation can be of benefit to both sows and newborn piglets.